Routes and barriers associated with protein and peptide drug delivery system - Saba Saeed; Mavra Irfan; Saima Naz; Momil Liaquat; Shafaq Jahan; Sana Hayat (Journal of the Pakistan Medical Association, 2021)
Published in August 2021